Integrated Assessment of Metal Contamination of Soils, Sediments, and Runoff Water in a Dry Riverbed from a Mining Area Under Torrential Rain Events - José Cuevas; Ángel Faz; Silvia Martínez-Martínez; Juan Beltrá; José A. Acosta (Land)
Dry riverbeds can transport mining waste during torrential rain events, disseminating pollutants from mining areas to natural ecosystems. This study evaluates the impact of these mine wastes on soils, sediments, and runoff/pore water in the La Carrasquilla dry riverbed (southeastern Spain). An integrated approach utilizing geochemical and mineralogical techniques was employed, analyzing water, soil, and sediment samples from both the headwater and mouth of the riverbed. Soil profiles and pore water were collected at 30 cm, 60 cm, and 90 cm deep, alongside sediment and runoff water samples. The assessment of metal(loid) contamination focused on arsenic, cadmium, chromium, copper, iron, nickel, manganese, zinc, and lead, utilizing sequential extraction to evaluate metal partitioning across soil phases. Various pollution indices, including the contamination factor (Cf), pollution load index (PLI), potential ecological risk index (RI), and metal(loid) evaluation index (MEI), were employed to classify contamination levels. The highest level of contamination was reported in the headwater, which suggested anthropogenic activities linked to the presence of mining residues as the major source of metal(loid)s. However, an active deposition of As, Cd, Cu, Fe, Mn, and Zn was reported in the topsoil at the mouth. In the headwater, a quartz and muscovite-rich zone exhibited the highest Cf for Pb (1022), primarily bound to the soil residual fraction (62.8%). At the headwater and mouth, pore water showed higher concentrations of sulfate, Ca, Na, Cl, Mg, and Mn and higher salinity than acceptable limits for drinking water or irrigation established by the World Health Organization. Runoff-water metal concentrations surpassed established guidelines, with MEI values indicating significant contamination by cadmium (36.1) and manganese (19.0). These findings highlight the considerable ecological risk of Pb and underscore the need for targeted remediation strategies to mitigate environmental impacts in the Mar Menor coastal lagoon.